2015
DOI: 10.1007/978-94-017-7342-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Reliance of Pavement Texture Characteristics on Mix-Design and Compaction Process

Abstract: The surface texture in Hot Mix Asphalt (HMA) pavements has an important role respect to all functional performances: wet and dry friction, rolling noise generation, tire wear, and so on. The texture of a new pavement is a consequence of HMA composition (mix-design) and of construction techniques, especially considering the compaction process. While numerous studies have investigated the effect of mix design on texture, it is still unclear the effect of construction techniques. In this research, some experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The construction costs of rigid pavements are generally more expens than asphalt pavements, especially if a high level of surface regularity is required [13]. However, t are suitable for high shear stresses, or concentrated vertical loads, or areas subjected to fuel spilla which can result in structural or functional distresses on asphalt pavements [14,15]. Maintena management of a rigid pavement is less frequent and expensive compared to a flexible pavement Block pavements are appropriate for prolonged stationing areas due to their resistance concentrated loads [16].…”
Section: Recommended Solutionmentioning
confidence: 99%
“…The construction costs of rigid pavements are generally more expens than asphalt pavements, especially if a high level of surface regularity is required [13]. However, t are suitable for high shear stresses, or concentrated vertical loads, or areas subjected to fuel spilla which can result in structural or functional distresses on asphalt pavements [14,15]. Maintena management of a rigid pavement is less frequent and expensive compared to a flexible pavement Block pavements are appropriate for prolonged stationing areas due to their resistance concentrated loads [16].…”
Section: Recommended Solutionmentioning
confidence: 99%
“…Pavements contribute to ensuring the safe and efficient operation of transport infrastructures [ 1 , 2 ]; they should be monitored over time, in order to prevent severe distresses due to the vertical and tangential forces transmitted by the aircraft, and thermo-hygrometric conditions [ 3 ]. The evaluation and prediction of the functional and structural performance of the pavements play a pivotal role in guaranteeing safety and regularity of operations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the maximum temperatures of the permeable asphalt pavement and traditional asphalt pavement is defined as the cooling performance of permeable asphalt pavement. In the long-term use of permeable pavement, the study found that it was easily affected by the environment and the compaction conditions, leading to void clogging [6][7][8], weakening its permeability characteristics, and also affecting the cooling performance.…”
Section: Introductionmentioning
confidence: 99%